(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides a systematic and in-depth analysis of the semantic features of landscape terminology in Uzbek and English. The primary objective of the study is to examine the linguistic characteristics of landscape terms in their contemporary usage across the two languages and to identify their correlations with various cultural, historical, and linguistic factors. The research investigates the lexical-semantic structure of the terms, identifies their synonymic series, semantic parallels, linguistic variations, and terminological distinctions. The frequency of use, functional features, and contextual connections of landscape terminology are analyzed using linguistic and statistical methods. Specifically, methods of textology, corpus linguistics, and semantic analysis are applied to uncover the practical aspects of the functioning of linguistic units in modern discourse. This approach provides both theoretical and practical insights into the commonalities and distinctions of landscape terminology in Uzbek and English. The study results contribute to a deeper understanding of the mutual influence of terminological bases in the two languages, the exploration of the linguistic evolution of landscape terms, and the foundation for broader and more detailed study of terminological units in this field. This work not only enriches the theoretical framework for linguistic research but also expands the possibilities for its practical application.